Bioactive peptides and antinutrients in chickpea: description and properties (a review) - M. Ahangaran; D. A. Afanasev; I. M. Chernukha; N. G. Mashentseva; M. Gharaviri (Труды по прикладной ботанике, генетике и селекции)
Legumes are a rich source of many different biologically active substances, such as fiber, proteins, vitamins and minerals. Chickpea (Cicer arietinum L.) is the third most important leguminous plant in the world: it has high nutritional value and is a source of a wide range of bioactive compounds. Bioactive peptides of chickpea seeds have antioxidant, ACE-inhibiting, cholesterollowering, antihypertensive, antimicrobial, antithrombotic, immunomodulatory, and opioid activities as well as the ability to bind minerals. But despite the benefits and high nutritional value, chickpea seeds contain antinutrients that reduce their nutritional and biological advantages. These antinutritional factors include condensed tannins, raffinose, and phytic acid. Research has shown that cooking, pregermination or fermentation can effectively reduce the indigestible content of chickpea seeds. For this purpose, it is recommended to use certain physical, chemical or biological methods: heat treatment, soaking and/or germination, enzymatic hydrolysis, irradiation, etc.This review article presents the world’s results of research aimed at studying bioactive chickpea peptides derived from chickpea seeds and ways of their formation as well as methods for elimination of antinutritional factors.